2019
DOI: 10.1111/jen.12605
|View full text |Cite
|
Sign up to set email alerts
|

Preliminary survey on putative insect vectors for Rubus stunt phytoplasmas

Abstract: Phytoplasmas are cell wall‐less phytopathogenic bacteria which are associated with a disease in Rubus species known as Rubus stunt. Symptoms range from stunting, witches’ broom, small leaves, short internodes, enlarged sepals, phyllody and flower proliferation to fruit malformations. Phytoplasmas can be spread by vegetative propagation and by phloem‐feeding insect vectors. However, little is known about the spectrum and distribution of putative Rubus stunt insect vectors. In this study, a screening of putative… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 32 publications
0
4
0
Order By: Relevance
“…Macrosteles quadripunctulatus and A. ribauti have been reported as vectors of ‘ Candidatus Phytoplasma solani’ (Battle, Altabella, Sabate, & Laviňa, ; Riedle‐Bauer, Sara, & Regner, ) which infects a wide range of wild and cultivated plants, while Fieberiella florii is a vector of ‘ Candidatus Phytoplasma mali’ which represents one of the most economically important threats to apple trees (Tedeschi & Alma, ). Furthermore, Arboridia adanae and Zygina rhamni are considered serious grape pests in Eastern Mediterranean regions and in Europe (Olivier et al, ) while various leafhoppers are vectors of phytoplasmas in Rubus species (Linck & Reineke, ). Lastly, it is worth stating that the species Anaconura acuticeps of the subfamily Deltocephalinae and the species A. adanae and Z. rhamni of the subfamily Typhlocybinae are recorded for the first time in Greece.…”
Section: Discussionmentioning
confidence: 99%
“…Macrosteles quadripunctulatus and A. ribauti have been reported as vectors of ‘ Candidatus Phytoplasma solani’ (Battle, Altabella, Sabate, & Laviňa, ; Riedle‐Bauer, Sara, & Regner, ) which infects a wide range of wild and cultivated plants, while Fieberiella florii is a vector of ‘ Candidatus Phytoplasma mali’ which represents one of the most economically important threats to apple trees (Tedeschi & Alma, ). Furthermore, Arboridia adanae and Zygina rhamni are considered serious grape pests in Eastern Mediterranean regions and in Europe (Olivier et al, ) while various leafhoppers are vectors of phytoplasmas in Rubus species (Linck & Reineke, ). Lastly, it is worth stating that the species Anaconura acuticeps of the subfamily Deltocephalinae and the species A. adanae and Z. rhamni of the subfamily Typhlocybinae are recorded for the first time in Greece.…”
Section: Discussionmentioning
confidence: 99%
“…1A). Few studies have reported leafhoppers in strawberries and raspberries (Linck and Reineke 2019). However, a new study from our group identified a high diversity of leafhoppers in strawberry fields (Plante et al 2023), evidence that the low number of reports might not be linked to host preference but probably to the economic importance of other crops and/or relevant phytoplasma diseases detected affecting those crops, and therefore, demanding primary studies (e.g., blueberry and lingonberry stunt phytoplasma diseases, grapevines yellows disease, and strawberry green petal disease) (Olivier et al 2014, Arocha-Rosete et al 2015, 2019, Pérez-López et al 2019, Hammond et al 2021, Brochu et al 2022, Plante et al 2023).…”
Section: Leafhoppers Phytoplasma and Berries In The Last Decade In Ca...mentioning
confidence: 99%
“…Despite being reported as a common leafhopper on raspberry in the Netherlands [ 74 ], it has been noted from Germany and Italy that M. fuscula and other Macropsis spp. are quite rare on raspberry and blackberry [ 96 , 97 ].…”
Section: Known and Potential Invertebrate Vectors Of Raspberry Virusesmentioning
confidence: 99%